Effectiveness of the use of subjective techniques to achieve safe cuff pressures in artificial airway devices: a systematic review - Rosales Lillo, Felipe; Monichi Valdenegro , Giovanna (Revista de Investigación en Logopedia, 2026)
In patients with artificial airways, adequate airway sealing is crucial, achieved by managing cuff pressures. Subjective techniques lack measurable values and remain controversial. While objective methods are ideal, resource-limited settings often rely on subjective techniques, which could impact patient safety. This study aims to describe the effectiveness of subjective techniques in achieving safe cuff pressures in artificial airway devices. A systematic review with a qualitative approach was performed, including published evidence between 2024 and 2015 in PubMed, Web of Science and SciELO databases. The keywords ‘Techniques’, ‘Cuff’, ‘Intubation’, ‘Pressure’ and ‘Tracheostomy’ were included. Of 3,185 reviewed documents, 14 articles were selected for final analysis. PRISMA guideline was used for the report. Subjective techniques namely by digital palpation, minimal leak, predetermined volume, loss of resistance syringe and the minimal occlusive volume were studied. The evidence shows that these techniques reach a correct cuff pressure range between 4.40% and 76.46% of total cases. The digital palpation technique shows the worst success rate (4.40% to 27.27%). Furthermore, these methods result in both underinflation (2.00% and 26.30%) and overinflation (15.52% and 93.75%), with a stronger tendency towards the latter. In conclusion, subjective techniques are unreliable as they achieve unsafe cuff pressure range, which could be harmful during patient care. It is recommended that hospitals review and update their protocols by investing in and exclusively using manometers to ensure patients' safety. For countries and healthcare settings with limited access, low-cost, safe, and validated alternatives to manometers are urgently needed, instead of continuing the use of traditional subjective methods.
Keywords: Airway Management; Tracheostomy; Quality Assurance in Health Care; Intubation; Intratracheal